2019
DOI: 10.1177/0036850419878065
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of critical negative rake angle and friction characteristics in orthogonal cutting of AL1060 and T2

Abstract: The stagnant region often appears in front of the tool cutting edge, which is caused by mechanical inlay and excessive pressing in plastic metal cutting with large negative rake angle tools at a low speed. It results in the change of the effective negative rake angle which can affect the flow characteristics of material, the quality of machined surface and the abrasion loss of cutting tools. However, the critical negative rake angle model based on the existence of the stagnant region has not been reported yet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…This stagnant region is wrapped around the rounded-edge tool blade, which acts as the tool true surface. The simulation results are consistent with those obtained by the scholar Ohbuchi Y and Ding [6,11]. And the stagnant region change the flow characteristics of the material, meanly some materials flow up along the stagnant region to form chips at the speed of v1, and some materials flow down along the stagnant region to form the processed surface at the speed of v2.…”
Section: Figure 1 2d-orthogonal Cutting Fem Of the Rounded-edge Toolsupporting
confidence: 88%
“…This stagnant region is wrapped around the rounded-edge tool blade, which acts as the tool true surface. The simulation results are consistent with those obtained by the scholar Ohbuchi Y and Ding [6,11]. And the stagnant region change the flow characteristics of the material, meanly some materials flow up along the stagnant region to form chips at the speed of v1, and some materials flow down along the stagnant region to form the processed surface at the speed of v2.…”
Section: Figure 1 2d-orthogonal Cutting Fem Of the Rounded-edge Toolsupporting
confidence: 88%
“…Similar findings were obtained in which the interfacial friction force with a rake angle of 0 • was less than that with a rake angle of 20 • [109]. In addition, the critical negative rake angle was associated with the adhesive friction coefficient at the toolworkpiece interface [111]. The average friction coefficient increased and remained constant as the critical negative rake angle increased.…”
Section: Cutting Parameters and Tool Wearsupporting
confidence: 79%
“…Then, he also found the minimum negative rake angle is −65° in nanometric cutting of copper material [ 25 ]. Ding et al [ 26 ] found that the minimum negative rake angle is −77° in orthogonal cutting of AL 1060. Lai et al [ 27 ] reported that the minimum negative rake angle for chip formation of copper is between −65° and −70°.…”
Section: The Determination Of Minimum Undeformed Chip Thickness Bamentioning
confidence: 99%